Obstetric medicine care in South Europe. (September 2021) - Ateka-Barrutia, O; Palma dos Reis, I; Maina, A; Bezanahary, H
Obstetric medicine is an emerging area of interest within Internal Medicine in Europe. Despite that, "OM" is still an unpopular concept and an unrecognised subspecialty in South Europe. A considerable number of internists and medical specialists deal with maternal medical problems in association with obstetricians and other specialists on a daily basis. Due to their interest and mostly part-time dedication to maternal care, a growing mass of physicians are getting specific training in the field either locally or, less frequently, abroad, and are also building specific clinics, inpatient care services and other new bonds with obstetricians in numerous tertiary care centres. In this article, we aim to describe the state of the growing field of obstetric medicine in Portugal, Italy, France and Spain, the particular clinical, educational and academic efforts and steps that have recently been developed by internists in each country, as well as planned initiatives for the future.